Oncologic outcomes after nipple‐sparing mastectomy: A single‐institution experience. Issue 1 (2nd December 2015) - Frey, Jordan D.; Alperovich, Michael; Kim, Jennifer Chun; Axelrod, Deborah M.; Shapiro, Richard L.; Choi, Mihye; Schnabel, Freya R.; Karp, Nolan S.; Guth, Amber A.
Abstract : Introduction: Long‐term oncologic outcomes in nipple‐sparing mastectomy (NSM) continue to be defined. Rates of locoregional recurrence for skin‐sparing mastectomy (SSM) and NSM in the literature range from 0% to 14.3%. We investigated the outcomes of NSM at our institution. Methods: Patients undergoing NSM at our institution from 2006 to 2014 were identified and outcomes were analyzed. Results: From 2006 to 2014, 319 patients (555 breasts) underwent NSM. One‐hundered and fourty‐one patients (237 breasts) had long‐term follow‐up available. Average patient age and BMI were 47.78 and 24.63. Eighty‐four percent of patients underwent mastectomy primarily for a therapeutic indication. Average tumor size was 1.50 cm with the most common histologic type being invasive ductal carcinoma (62.7%) followed by DCIS (23.7%). Average patient follow‐up was 30.73 months. There was one (0.8%) incidence of ipsilateral chest‐wall recurrence. There were 0.37 complications per patient. Conclusions: We examined our institutional outcomes with NSM and found a locoregional recurrence rate of 0.8% with no nipple‐areolar complex recurrence. This rate is lower than published rates for both NSM and SSM. J. Surg. Oncol. 2016;113:8–11 . © 2015 Wiley Periodicals, Inc.